ANALISIS PERLINDUNGAN HUKUM KONSUMEN BAGI PENONTON BOLA DALAM TRAGEDI DI STADION KANJURUHAN - Din Eri Pratama; Rani Apriani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
The tragedy at the Kanjuruhan Stadium has claimed quite a number of victims, including 133 victims who died. This is certainly a special concern in the legal field, where victims need to be given legal protection. Legal protection is provided in the UUPK and UUKOR, and is based on criminal and civil law. This legal protection is further proven by the results of the investigation conducted by TGIPF in investigating the tragedy. This research is based on empirical events that were studied normatively with a library approach by processing secondary data deductively, in order to obtain in-depth information on how to protect consumers who are victims of the law. Keywords: Legal protection; Consumer protection; Victims of Tragedy at Kanjuruhan Stadium.